A constituição da ação criativa manifestada em uma formação com tecnologias digitais por professoras que ensinam matemática - Silva, Priscila Gleden Novaes da (2024)
The literature establishing a link between creativity and working with digital technologies in mathematics education has largely focused on examining how resources enhance creativity in mathematics, to the detriment of creativity when working with technologies in mathematics education. Among the research that specifically addresses creativity in pedagogical work with digital technologies, we highlight the lack of studies that address the aspects that permeate the constitution of creative acts within the pedagogical practice of mathematics teachers, as evidenced by the literature review presented in the format of multipaper thesis. We have investigated, based on Vlad Glăveanu's perspective of distributed creativity as a theoretical contribution: How are the possible creative acts of teachers who teach mathematics constituted when they participate in professional development with digital technologies? In this experiment, the research developed an in-service training with ten public school teachers who teach elementary school mathematics (nine in the initial years and one in the final years) in the state of Paraná. The training, based on the perspective of Cybereducation took place in three phases: Investigation of the characteristics and possibilities of technological resources, especially for teaching mathematics; planning of mathematics teaching activities with digital technologies and subsequent reflection on the implementation of practices with mathematics teaching activities with digital technologies. The analysis focused on the report and reflection on the development of practices with digital technologies carried out by the teachers. The data produced consisted of transcriptions of the participants' speeches recorded in moments of interaction during the report and the trainer's written notes (notes from the training sessions and observed classes) and were analysed in the light of content analysis. The results show that the teachers' creative acts include the intention to go further in their pedagogical work with digital technologies, giving a new meaning to their understanding and experiences with the resources, shaping the teachers' perspectives of action with these technologies through a dialogical opening to the students' perspective and reflection on their own practice. Thus, we emphasize that, from the perspective of developing teaching creativity in pedagogical work with digital technologies, educational practice must value these understandings and experiences and seek to extend them by promoting spaces where teachers can experience the possibilities of technological resources for the teaching and learning of mathematics, based on a dialog with students in the school context they experience, in order to advance what they have already imagined for teaching with technologies to develop and constitute students' mathematical knowledge.